The Role of Histone Deacetylases in NLRP3 Inflammasomesmediated Epilepsy - Kuang, Xi; Chen, Shuang; Ye, Qingmei (Current Molecular Medicine, 2024)
Epilepsy is one of the most common brain disorders that not only causes death worldwide, but also affects the daily lives of patients. Previous studies have revealed that inflammation plays an important role in the pathophysiology of epilepsy. Activation of inflammasomes can promote neuroinflammation by boosting the maturation of caspase-1 and the secretion of various inflammatory effectors, including chemokines, interleukins, and tumor necrosis factors. With the in-depth research on the mechanism of inflammasomes in the development of epilepsy, it has been discovered that NLRP3 inflammasomes may induce epilepsy by mediating neuronal inflammatory injury, neuronal loss and blood-brain barrier dysfunction. Therefore, blocking the activation of the NLRP3 inflammasomes may be a new epilepsy treatment strategy. However, the drugs that specifically block NLRP3 inflammasomes assembly has not been approved for clinical use. In this review, the mechanism of how HDACs, an inflammatory regulator, regulates the activation of NLRP3 inflammasome is summarized. It helps to explore the mechanism of the HDAC inhibitors inhibiting brain inflammatory damage so as to provide a potential therapeutic strategy for controlling the development of epilepsy.
Keywords: NLRP3 inflammasome